Энергетический баланс при наклонном падении излучения на плоский пространственно ограниченный слой - Горячев Б. В. Борис Валентинович; Кутлин А. П.; Ларионов В. В. Виталий Васильевич; Могильницкий С. Б. Сергей Борисович; Савельев Б. А. (Томск, 1983)
Деп. в ВИНИТИ 11.08.83, № 4414-83